Rethinking the Social through Durkheim, Marx, Weber and Whitehead. - Halewood, Michael (Key issues in modern sociology., 2014)
This is the first book to systematically analyse the different concepts of the social developed by Durkheim, Marx and Weber, suggesting that debates surrounding this concept are still very much alive